2015
DOI: 10.1073/pnas.1517246112
|View full text |Cite
|
Sign up to set email alerts
|

Temporal fate mapping reveals age-linked heterogeneity in naive T lymphocytes in mice

Abstract: Understanding how our T-cell compartments are maintained requires knowledge of their population dynamics, which are typically quantified over days to weeks using the administration of labels incorporated into the DNA of dividing cells. These studies present snapshots of homeostatic dynamics and have suggested that lymphocyte populations are heterogeneous with respect to rates of division and/or death, although resolving the details of such heterogeneity is problematic. Here we present a method of studying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
111
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(139 citation statements)
references
References 39 publications
15
111
3
Order By: Relevance
“…Nevertheless, these analyses suggest that CD4 + RTE have a life expectancy of just 3 weeks (95% CI: 12‐36 days), and that only an estimated 27% of them mature into naive T cells with a life expectancy of 2‐3 months. The resulting overall life expectancy of CD4 + naive T cells of 1/(0.5 × 0.046 + 0.5 × 0.015) = 33 days is shorter than that of CD8 + naive T cells, which is in good agreement with other mouse studies as well as human studies …”
Section: Naive T‐cell Dynamics In Humans and Micesupporting
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, these analyses suggest that CD4 + RTE have a life expectancy of just 3 weeks (95% CI: 12‐36 days), and that only an estimated 27% of them mature into naive T cells with a life expectancy of 2‐3 months. The resulting overall life expectancy of CD4 + naive T cells of 1/(0.5 × 0.046 + 0.5 × 0.015) = 33 days is shorter than that of CD8 + naive T cells, which is in good agreement with other mouse studies as well as human studies …”
Section: Naive T‐cell Dynamics In Humans and Micesupporting
confidence: 90%
“…Hogan et al suggested that the MN CD4 + and CD8 + T‐cell pools in mice have another layer of kinetic heterogeneity, in that most cells are readily replaced by new RTE, while a subpopulation of long‐lived “incumbent” cells are resistant to displacement by RTE and maintain themselves by peripheral division (with interdivision times of 167 and 213 days for CD4 + and CD8 + naive T cells, respectively, estimated with a model for Ki67 expression). Our data were also suggestive for the existence of such long‐lived cells within the CD8 + MN T‐cell pool, as a relatively high enrichment of CD8 + naive T cells was retained during the de‐labeling phase of the prenatal labeling experiments.…”
Section: Naive T‐cell Dynamics In Humans and Micementioning
confidence: 99%
“…Specifically, we modelled the kinetics of replacement of host cells by donor cells within the CD4 + CD25 − CD44 hi CD62L hi  and CD4 + CD25 − CD44 hi CD62L lo populations, termed CD4 central memory (CD4 T CM ) and CD4 effector memory (CD4 T EM ) respectively (Figure 2A), for over a year post-treatment. We previously demonstrated that the kinetics of lymphocyte replacement in the busulfan chimeras are a rich source of information regarding homeostatic turnover and population substructure (Hogan et al, 2015).
10.7554/eLife.23013.006Figure 2.Estimating constitutive rates of generation of CD4 T cell memory.( A ) Gating strategy for CD4 central and effector memory subsets.
…”
Section: Resultsmentioning
confidence: 99%
“…These quantities were logit-transformed to normalise residuals. Using the maximum likelihood estimates of the variance of the residuals in each of the timecourses, fitting a model of temporal heterogeneity to the BrdU/Ki67 timecourses therefore required maximising the product of the likelihoods of the two timecourses (See Supporting Information S2 in Hogan et al (2015) for a description) over four continuous parameters (β, ϵ, δ+, τ) and two discrete ones (truek^, trueb^).To model multiple subpopulations (kinetic heterogeneity, KH) we used replicates of Equations 14. This process increased the number of parameters to be estimated and so we explored a model of two distinct subpopulations only.…”
Section: Appendix 1—tablementioning
confidence: 99%
“…At thymus egress, naïve CD4 + T-cells feature unique phenotypic and functional properties (2, 13, 16, 76, 120). Moreover, in agreement with studies using manipulated murine models, the cell-intrinsic properties in terms of turnover, survival, and threshold for TCR activation is also modulated by prolonged time span in circulation (2, 8, 1012, 121).…”
Section: Naïve Cd4+ T-cell Heterogeneitymentioning
confidence: 99%